2012
DOI: 10.1021/es300058w
|View full text |Cite
|
Sign up to set email alerts
|

Level and Degradation of Deepwater Horizon Spilled Oil in Coastal Marsh Sediments and Pore-Water

Abstract: This research investigates the level and degradation of oil at ten selected Gulf saltmarsh sites months after the 2010 BP Macondo-1 well oil spill. Very high levels (10-28%) of organic carbon within the heavily oiled sediments are clearly distinguished from those in pristine sediments (<3%). Dissolved organic carbon in contaminated pore-waters, ranging up to hundreds of mg/kg, are 1 to 2 orders of magnitude higher than those at pristine sites. Heavily oiled sediments are characterized by very high sulfide conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 39 publications
(64 reference statements)
2
51
0
Order By: Relevance
“…The CPI values were also significantly different in 2013 compared to in 2010 and 2011 (see Table S2f in the supplemental material), but the Pr/Phy ratios increased and were comparable to May 2010 prespill ratios, thereby suggesting alkane degradation (63,68). Evidence of biodegradation was noted by others (38,40,69,70). By June 2013, the concentrations of n-alkanes and PAHs were 1 and 5%, respectively, of early 2011 concentrations, which confirmed that petroleum hydrocarbons were still present in the marshes, but at lower levels likely due to sediment sequestration, weathering, and degradation (68).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The CPI values were also significantly different in 2013 compared to in 2010 and 2011 (see Table S2f in the supplemental material), but the Pr/Phy ratios increased and were comparable to May 2010 prespill ratios, thereby suggesting alkane degradation (63,68). Evidence of biodegradation was noted by others (38,40,69,70). By June 2013, the concentrations of n-alkanes and PAHs were 1 and 5%, respectively, of early 2011 concentrations, which confirmed that petroleum hydrocarbons were still present in the marshes, but at lower levels likely due to sediment sequestration, weathering, and degradation (68).…”
mentioning
confidence: 63%
“…Initially, some DWH spill researchers proposed a swift microbial response (16,17) because microbes have the capacity to degrade constituent carbon compounds in oil (31)(32)(33)(34)(35) and earlier nutrient enrichment, metal exposure, and oiling experiments provided evidence that marsh communities could withstand low levels of disturbance from an oil spill (25,36). Short-duration studies based on research conducted during one sampling time or from Ͻ6 to 9 months of sampling events in 2010 and 2011 confirmed that the relative abundances and species richness for bacterial communities exposed to weathered oil residues changed through time and recognized a greater diversity among known hydrocarbon-degrading bacteria as the amount of petroleum hydrocarbon concentrations increased (37)(38)(39)(40). Although a cascading series of long-term biogeochemical consequences, due to the microbial response, was anticipated for the marsh ecosystem (41), some of the earlier studies suggested a faster-than-expected recovery (16,42).…”
mentioning
confidence: 93%
“…The most abundant microorganisms enriched both in the anodic and in the bulk communities were SRB, some of which were phylogenetically related to known anaerobic hydrocarbon degraders. This is logical if the environmental conditions are taken into account; oxygen is quickly depleted when an oil spill occurs due to the prominent presence of organic matter (75), while under anaerobic conditions sulfate reduction typically is enhanced (75). Toluene degradation rates under sulfate-reducing conditions can vary by orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, salt marsh organisms were exposed to weathered and dispersed 74 sweet crude oil, and oil-derived compounds (Natter et al, 2012;Stout et al, 2016). This resulted 75 in extensive mortality of saltmarsh plants, particularly in heavily oiled areas (Lin and 76 Mendelssohn, 2012).…”
Section: Introduction 70mentioning
confidence: 99%